The influence of inlet to outlet width ratio on The hydraulic performance of piano key weir (PKW-type A). Issue 6 (25th May 2022) - Mero, Shimal Khalid; Haleem, Dilshad Abdul Jabbar; Yousif, Ali Abduljabbar
Abstract: A piano key weir (PKW) is a modified version of non-linear weirs and it can be obtained via amending the centerline length of the weir by a small footprint. It is developed to increase the hydraulic performance of the linear weirs via increasing the pass discharge and the energy dissipation. A laboratory investigation is conducted on five physical PKW (Type A) models to investigate the effect of inlet to outlet width ratio (Wi/Wo) on the hydraulic performance of PKWs. The results showed that the (Wi/Wo) ratio has a predominant influence on the hydraulic performance of PKW. It was found out that the best hydraulic performance was obtained with Wi/Wo ratio equal to 1.25 among other investigated Wi/Wo ratios because the discharge coefficient was the highest for the given discharge and head. Further, the results revealed that the variation of Wi/Wo ratio from 1.25 had a negative impact on both discharge coefficient and efficiency. It was found out that the percentages of reduction in discharge coefficient when Wi/Wo=0.8, 1, 1.5% and 2 were 11%, 6%, 2% and 8%, respectively in comparison with the Wi/Wo=1.25. Similarly, for these Wi/Wo ratios, the percentages of reduction in discharge decrease by 11%, 6.5%, 2.35% and 9%, respectively, relatively to Wi/Wo=1.25. The linear regression equations' coefficients for the PKW models varied from 0.983 to 0.994, which means the performance of the models are good for the given Wi/Wo ratios. HIGHLIGHTS: The study was conducted in a laboratory that has a big open channel, which means the physical model scale is preferable by hydraulic community. Merging the piano key weir within the existing spillway structure in the dams becomes a necessary action to be performing since the flash flood increased due to the climate change. This aids enhancement.